Implementasi Metode Regresi Linear Berganda Dalam Memprediksi Santri Baru Di Pondok Pesantren Al-Falah Sumber Gayam - Khalishatus Shafariyah; Siti Khotijah (Department of Mathematics, Faculty of Mathematics and Scince, Universitas Annuqayah, 2025)
Al-Falah Islamic Boarding School Sumber Gayam, Kec. Kadur, Kab. Pamekasan is one of the boarding schools that fluctuates in terms of the number of new students each year. Therefore, predictions are very necessary to find out the number of new students who will register in the following year. The aim is to help the committee for accepting new students to be ready to prepare the boarding facilities as well as possible. The multiple linear regression method is the method used in this research to predict future conditions using previous data and to determine whether or not there is an influence exerted by the independent variable on the dependent variable. Annual student alumni data, boarding school facilities, annual fees and data on outstanding students are variables that are thought to influence the number of new students in 2023-204 by calculating MAPE and RMSE errors. The results of the research obtained as many as 98 new students based on testing the r2, r, F test and t test based on the sig value. < 0.05 which was calculated manually and SPSS version 26 calculations. The results show that the variables studied have a significant effect on the number of new students registering in 20232024 with a MAPE accuracy of 0.02% and an RMSE accuracy of 0.66%, this shows that the ability of the forecasting model formed can be said to be good or accurate.